Determinants of Islamic Banks' Net Income in Middle Eastern Countries - Suriani Suriani; Dewi Ayu Muliani; Chenny Seftarita (Share: Jurnal Ekonomi dan Keuangan Islam, 2022)
ABSTRACT – Income is one of the most important performance indicators for Islamic banks; the higher the income, the better their performances. Among all Islamic financial institutions worldwide, Islamic banks in the Middle East are listed as having the largest assets and income. This study examined how inflation, total assets, foreign investment (FDI), and gross domestic product (GDP) affect Islamic bank net income in the Middle East. The research objects are Islamic banks in the Middle East, with the criteria being the oldest Islamic banks with the largest assets, as determined by the IFSB report. The data were collected on an annual basis (2005-2021) and analyzed with the Panel Vectorautoregressive method. The results show that the current income of Islamic banks will have both positive and negative effects one year earlier. Meanwhile, gross domestic product had a negative impact on the net income of Islamic banks in Middle Eastern countries during the previous two years, whereas total assets had a positive impact during the same time period. In addition, neither inflation nor FDI has any effect on net income. The accumulated assets of Islamic banks in the Middle East are substantial and can be used to increase their net income. Additionally, the GDP has a negative impact on the net income of Islamic banks. This demonstrates that enhancement income from the public did not flow to Islamic banks, but rather was redirected to safer, more profitable, and less risky sectors, such as mutual funds, real estate, and stocks. Therefore, an increase in GDP as well as total assets is necessary in order to increase Islamic banks' net income in the Middle East.========================================================================================================ABSTRAK – Determinan Pendapatan Bersih Bank Syariah di Negara Timur Tengah. Pendapatan adalah salah satu indikator kinerja yang penting bagi bank syariah dimana semakin tinggi nilai incomenya, semakin baik pula kinerjanya. Di antara semua lembaga keuangan syariah di dunia, bank-bank syariah di Timur Tengah tercatat memiliki aset dan pendapatan terbesar. Penelitian ini bertujuan mengindentifikasi pengaruh inflasi, total aset, penanaman modal asing, dan produk domestik bruto (PDB) terhadap pendapatan bersih bank syariah di Timur Tengah. Objek penelitian adalah bank syariah di Timur Tengah dengan kriteria menjadi bank tertua dengan aset terbesar yang ditentukan oleh laporan IFSB. Data dikumpulkan secara tahunan (2005-2021) dan dianalisis dengan metode Panel Vectorautoregessive. Hasil kajian menunjukkan bahwa pendapatan bank syariah saat ini akan memiliki efek positif dan negatif satu tahun sebelumnya. Sementara itu, produk domestik bruto berdampak negatif terhadap pendapatan bersih bank syariah di negara-negara Timur Tengah selama dua tahun sebelumnya, sedangkan total aset berdampak positif dalam periode yang sama. Selain itu, baik inflasi maupun penanaman modal asing tidak berpengaruh terhadap pendapatan bersih. Akumulasi aset bank syariah di Timur Tengah sangat besar dan dapat digunakan untuk meningkatkan pendapatan bersih mereka. Kajian juga menunjukkan bahwa PDB memiliki dampak negatif terhadap pendapatan bersih bank syariah. Hasil ini mengindikasikan bahwa pendapatan masyarakat tidak masuk ke bank-bank syariah, tetapi mengalir ke sektor-sektor yang lebih aman, menguntungkan, dan kurang berisiko, seperti reksa dana, real estate, dan saham. Oleh karena itu, peningkatan PDB serta total aset diperlukan untuk meningkatkan laba bersih bank syariah di Timur Tengah.